Early phase mixed chimerism in bone marrow does not affect long-term outcomes of myeloablative single-unit cord blood transplantation for adult patients with hematological malignancies. Issue 12 (1st December 2016) - Konuma, Takaaki; Kato, Seiko; Oiwa-Monna, Maki; Ishii, Hiroto; Tojo, Arinobu; Takahashi, Satoshi
Abstract: Coexisting hematopoiesis from donor and recipient origin, called a mixed chimerism status, can occur in patients after myeloablative allogeneic hematopoietic stem cell transplantation. However, its impact on the outcomes of cord blood transplantation (CBT) has yet to be clarified. We retrospectively analyzed 150 adult patients who received myeloablative single-unit CBT for hematological malignancies in our institute. At the median time of first bone marrow analysis of 41 days after CBT, mixed chimerism was observed in 16 of the 150 patients. Among patients with mixed chimerism, 4 patients relapsed. The remaining 12 patients were alive and in remission at a median follow-up of 50 months. Bone marrow-mixed chimerism did not have a significant impact on the incidences of disease-free survival, relapse, or transplant-related mortality after CBT. These data show that early phase mixed chimerism did not have a significant impact on long-term outcomes after myeloablative single-unit CBT for hematological malignancies.